2017
DOI: 10.1186/s12884-017-1294-8
|View full text |Cite
|
Sign up to set email alerts
|

An abdominal ectopic pregnancy following a frozen-thawed ART cycle: a case report and review of the literature

Abstract: BackgroundEctopic pregnancy (EP) occurs in 1% of pregnancies and is reported to be more common in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) pregnancies. An abdominal ectopic pregnancy (AEP) is a rare form of EP, and there are few reports of an AEP after IVF/ICSI. In this case report, a rare case of AEP after frozen-thawed cycle of ICSI is presented.Case presentationAfter a frozen-thawed cycle of ICSI, the beta-human chorionic gonadotropin (HCG) level at 4 weeks 0 days of gestation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…[ 6 ] An increasing number of studies have shown IVF is one of the risk factors leading to abdominal pregnancy. [ 7 9 ] Although a majority of pregnancy could be visualized on TVS, ultrasonography alone is rarely used because yolk sac do not develop to this stage and exceedingly rare abdominal pregnancy may not identified. [ 10 ] Thus, it is important to monitor the serum β-hCG level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] An increasing number of studies have shown IVF is one of the risk factors leading to abdominal pregnancy. [ 7 9 ] Although a majority of pregnancy could be visualized on TVS, ultrasonography alone is rarely used because yolk sac do not develop to this stage and exceedingly rare abdominal pregnancy may not identified. [ 10 ] Thus, it is important to monitor the serum β-hCG level.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] And there were 3 similar abdominal pregnancies from 2000 to 2020 (Table 1 ). [ 9 , 15 , 16 ] These cases have common characteristics: the history of IVF failure and the delayed serum β-hCG rise. It is suspected that a small number of embryos may lead slower proliferative activity of the trophoblast tissue and the abnormal implantation site may cause the poor absorption of β-hCG into the blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, a poorly implanted or dying ectopic pregnancy may be present, in consequence of which the pregnancy test may be negative [ 10 ]. Another rare case presented with a very low serum β-HCG level of 3.4 IU/L was also reported to develop an AEP after hormone replacement frozen-thawed cycle [ 11 ]. A woman was also reported having undetectable serum β-hCG 9 days after blastocyst transfer, and was then diagnosed with a ruptured AEP and intra-abdominal bleeding 19 days later [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…La presentación clínica de las gestaciones ectópicas suele resultar muy inespecífica 10 . Actualmente la ecografía transvaginal es el método más sensible y específico para el diagnóstico precoz del embarazo ectópico 11,12,13 . La combinación de la ecografía transvaginal con la determinación de β-HCG nos permite establecer el diagnóstico de forma más temprana y precisa, así como orientar la actitud terapéutica en cada caso 14 .…”
Section: Discussionunclassified